An outbreak of waterborne cryptosporidiosis caused by post-treatment contamination. - Smith, H. V. (Cambridge University Press, 1989)
An outbreak of waterborne cryptosporidiosis affecting 27 persons, diagnosed stool positive, occurred in Ayrshire in April 1988. Twenty-one in 27 confirmed cases required some form of fluid replacement therapy. Local general practitioners indicated a two- to fivefold increase in diarrhoeal disease during the outbreak, and following enquiries made by Environmental Health Officers it became apparent that many hundreds of people had suffered a diarrhoeal illness at that time. Cryptosporidium spp. oocysts were detected in the treated chlorinated water supply system, in the absence of faecal bacterial indicators. Oocyst contamination of a break-pressure tank containing final water for distribution was the cause of this waterborne outbreak. An irregular seepage of oocyst-containing water, which increased during heavy rains, was the cause of the break-pressure tank contamination, rather than a failure of the water-treatment processes. The waterborne route should be considered when clusters of cryptosporidiosis-associated with potable water occur. Waterborne cryptosporidiosis can occur in the absence of other faecal indicators of contamination.